2011
DOI: 10.1007/s00418-011-0846-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G protein-coupled estrogen receptor (GPER) and nuclear steroid hormone receptors by gonadotropins in human granulosa cells

Abstract: Estradiol and progesterone mediate their actions by binding to classical nuclear receptors, estrogen receptor α (ERα) and estrogen receptor β (ERβ) and progesterone receptor A and B (PR-A and PR-B) and the non-classical G protein-coupled estrogen receptor (GPER). Several animal knock-out models have shown the importance of the receptors for growth of the oocyte and ovulation. The aim of our study was to identify GPER in human granulosa cells (GC) for the first time. Moreover, the effect of different doses of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 49 publications
2
19
0
1
Order By: Relevance
“…Luteinizing hormone was recently shown to regulate GPER expression at the mRNA and protein level in human granulosa cells (Pavlik et al, 2011). Interactions and cross-talk between GPER and growth factor receptors, particularly EGFR and IGFR, have been recently summarized by Maggiolini and colleagues (Bartella et al, 2012; Lappano et al, 2013).…”
Section: Interactions Of Gper With Other Receptorsmentioning
confidence: 99%
“…Luteinizing hormone was recently shown to regulate GPER expression at the mRNA and protein level in human granulosa cells (Pavlik et al, 2011). Interactions and cross-talk between GPER and growth factor receptors, particularly EGFR and IGFR, have been recently summarized by Maggiolini and colleagues (Bartella et al, 2012; Lappano et al, 2013).…”
Section: Interactions Of Gper With Other Receptorsmentioning
confidence: 99%
“…It supports the unexpected results related to peritubular cells. The specificity of the antiserum was further substantiated by results of Western blotting experiments using human granulosa cells, recently reported to express GPER (Pavlik et al ., 2011; results not shown). To our knowledge GPER expression by the smooth-muscle-like peritubular cells of the testis has not been reported in previous studies using different antibodies and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 86%
“…Recently a non-classical G protein-coupled estrogen receptor (GPER) was described (Revankar et al 2005;Thomas et al 2005b), indicating that estradiol can act rapidly independent of transcription. With no data available regarding the expression of GPER in human granulosa tissue and cells, Pavlik et al (2011) addressed this issue and could identify in their study GPER in human granulosa cells (GC). The authors additionally demonstrated that high concentrations of LH increased GPER protein expression.…”
Section: Reproductive System (Female)mentioning
confidence: 99%